The Effect Of Self-Efficacy, Employee Well-Being and JOB Enrichment On Employee Performance at PT Berkatama Mulia Saputra Sidoarjo - Dwi Indra Lesmana; Tan Evan Tandiyono (International Forum of Researchers and Lecturers, 2025)
The current phenomenon serves as the foundation for our study. Finding out how self-efficacy, employee well-being, and job enrichment affect PT Berkatama Mulia Saputra Sidoarjo's employee performance is the aim of this study. This study is quantitative in nature and employs a sample of 46 employees. The Self Efficacy calculation produced a t-value of 4.558 and a probability value of Sig 0.000 <0.05. This implies that the self-efficacy component has a favourable and considerable impact on employee performance.A probability value of Sig 0.042 <0.05 and a t-value of 4.099 were derived from the Employee Well-Being calculation. This indicates that the employee well-being variable has a positive and significant impact on employee performance.The computation results show that the Job Enrichment variable has a probability value of Sig 0.000 <0.005 and a t-value of 7.948. This indicates that the job enrichment variable has a favourable and significant impact on employee performance.